Penerapan Aplikasi Mobile Untuk Mencari dan Memberikan Pertolongan Terhadap Kerusakan Pada Kendaraan Berdasarkan Lokasi Terdekat - Jihan Fadhilah; Dwiny Meidelfi; Aldo Erianda (Journal of Applied Computer Science and Technology, 2020)
For motor vehicles and cars, each year always causes an increase in the number of motor vehicle problems such as leaky tires, running out of gas or breaking down and the number of problems always increases. Where when these problems occur drivers always have difficulty in finding the nearest workshop or help. To seek help for problems with vehicles in the city of Padang, through mobile devices becomes very important considering vehicle users who find it difficult to find help. In this study the author tries to resolve the above problems by creating an Android-based system that makes it easy for motorists and cars to find help with the problems they are experiencing later. In the study of this mobile application the author will utilize GPS on existing smartphones so that they can search for other people who are around the location to make it easier to find the nearest aid provider. The study was conducted from the stages of needs analysis, design, implementation, until testing.